Putting Public Health Ethics into Practice: A Systematic Framework - Marckmann, Georg; Schmidt, Harald; Sofaer, Neema; Strech, Daniel (Frontiers in Public Health, 2015)
It is widely acknowledged that public health practice raises ethical issues that require a different approach than traditional biomedical ethics. Several frameworks for public health ethics have been proposed, however, none of them provides a practice-oriented combination of the two necessary components: (1) A set of normative criteria based on an explicit ethical justification and (2) a structured methodological approach for applying the resulting normative criteria to concrete public health issues. Building on prior work in the field and integrating valuable elements of other approaches to public health ethics, we present a systematic ethical framework that shall guide professionals in planning, conducting, and evaluating public health interventions. Based on a coherentist model of ethical justification, the proposed framework contains (1) an explicit normative foundation with five substantive criteria and seven procedural conditions to guarantee a fair decision process, and (2) a six-step methodological approach for applying the criteria and conditions to the practice of public health and health policy. The framework explicitly ties together ethical analysis and empirical evidence, thus striving for evidence-based public health ethics. It shall provide normative guidance to those who analyze the ethical implications of public health practice including academic ethicists, health policy makers, health technology assessment bodies, and public health professionals. It will enable those who implement a public health intervention and those affected by it (i.e. the target population) to critically assess whether and how the required ethical considerations have been taken into account. Thereby, the framework can contribute to assuring the quality of ethical analysis in public health. Whether the presented framework will be able to achieve its goals has to be determined by evaluating its practical application.